Strength and stiffness performance of geopolymer stabilized washed recycled sands derived from demolition wastes in pavement subgrades - Xue, Yunxin (2024)
In this research study, geopolymer stabilized washed recycled sand (RS) derived from construction and demolition (C&D) waste was evaluated to effectively address issues related to the landfilling of wastes and the unsustainable usage of virgin sand quarry materials. This study evaluated the feasibilities of stabilizing washed RS with geopolymers and their subsequent usage as pavement subgrade materials. Industrial by-products comprising of fly ash (FA), granulated blast furnace slag (S), and the combination of (FA + S) were considered as three different precursors in the geopolymer stabilization of RS. The strength performance of geopolymers stabilized RS for each precursor was investigated through the unconfined compressive strength (UCS) and scanning electron microscopy (SEM) tests. Geopolymer stabilized samples with S were found to exhibit a generally higher UCS strength than FA-based samples. Yet the curing time was found to be important in geopolymerization process, that commonly longer the curing periods, higher the UCS strength. The chemical reaction of S-based geopolymer required a considerable amount of water to take place. A strength drop was therefore noticed in S-related instances at longer curing period due consideration of the water consumption during the geopolymerization process. As such, under cases of when an excess amount of S was added to the sample, when a high curing temperature was used or when longer curing durations were implemented. The highest UCS value attained among the tested samples was 22.024 MPa, when a precursor of 15 % FA + 15 % S was used and when cured for 7 days at 40 °C. A repeated load triaxial (RLT) test was carried out to further prove that the geopolymer stabilized washed RS could substitute the role of quarried sands in pavement. Under the curing condition of 7 days at 21 °C, samples stabilized with 30 % FA or 10 % S were found to be stiff enough to respond to the axial stress change under the same confining condition.